2022
DOI: 10.1007/s00429-022-02502-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in resting-state functional connectivity after brain posterior lesions reflect the functionality of the visual system in hemianopic patients

Abstract: Emerging evidence suggests a role of the posterior cortices in regulating alpha oscillatory activity and organizing low-level processing in non-alpha frequency bands. Therefore, posterior brain lesions, which damage the neural circuits of the visual system, might affect functional connectivity patterns of brain rhythms. To test this hypothesis, eyes-closed resting state EEG signal was acquired from patients with hemianopia with left and right posterior lesions, patients without hemianopia with more anterior le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
(151 reference statements)
0
3
0
Order By: Relevance
“…Therefore, it still needs to be elucidated whether prolonged trains of sensory entrainment, unlike short-lasting ones, may result in more diffused and long-lasting effects that may extend to ipsilateral brain regions and/or other brain areas. This might be of particular interest in light of well-documented evidence showing alterations in the posterior alpha oscillations [120][121][122], as well as dysfunctions in alpha-band activity in large-scale networks, associated with cognitive and sensory impairments ( [123][124][125]; Table 2). Indeed, occipito-parietal alpha rhythm has been consistently shown to reflect the reliable neurophysiological signature of the sensory and cognitive functionality in individuals with neuropsychiatric disorders (for a review, see: [117,123,124]), such as autism spectrum disorders (ASD) [125] or schizophrenia spectrum disorders (SSD).…”
Section: Alpha-band Sensory Entrainment: Long-term Effects and Clinic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it still needs to be elucidated whether prolonged trains of sensory entrainment, unlike short-lasting ones, may result in more diffused and long-lasting effects that may extend to ipsilateral brain regions and/or other brain areas. This might be of particular interest in light of well-documented evidence showing alterations in the posterior alpha oscillations [120][121][122], as well as dysfunctions in alpha-band activity in large-scale networks, associated with cognitive and sensory impairments ( [123][124][125]; Table 2). Indeed, occipito-parietal alpha rhythm has been consistently shown to reflect the reliable neurophysiological signature of the sensory and cognitive functionality in individuals with neuropsychiatric disorders (for a review, see: [117,123,124]), such as autism spectrum disorders (ASD) [125] or schizophrenia spectrum disorders (SSD).…”
Section: Alpha-band Sensory Entrainment: Long-term Effects and Clinic...mentioning
confidence: 99%
“…In addition, alterations in alpha rhythm were shown to predict the structural and functional integrity of the visual system in patients affected by posterior brain damage. In particular, recent investigations regarding hemianopic and neglect patients revealed that, although residual alpha activity can be observed in response to stimuli in the blind/neglected field [145,146], these clinical populations show dysfunctional neuronal oscillatory dynamics in the alpha band, characterized by a slowdown of IAF [120,147] and a decrease in the alpha power [120,122] and connectivity [121,148] in the lesioned hemisphere that were associated with impaired visual performance in the blind and in the neglected field [120][121][122][147][148][149], strengthening the notion that post-lesional variations in alpha oscillatory activity could represent a reliable biomarker of the functionality of the visual system. In light of this evidence, prolonged alpha-band sensory entrainment protocols may represent a potential effective tool for modulating the residual impaired alpha oscillatory activity, leading to enhanced visual perceptual performance by means of the plastic reorganization of the underlying oscillating networks in these patients.…”
Section: Alpha-band Sensory Entrainment: Long-term Effects and Clinic...mentioning
confidence: 99%
“…Gallina et al. ( 2022 ) showed that postchiasmal lesions in posterior cortices specifically lead to stronger impairments of FC in the alpha range. Allaman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Pedersini et al (2020) demonstrated that a functional reorganization of the brain in hemianopic patients occurred, compensating for the general reduced connectivity. Gallina et al (2022) showed that postchiasmal lesions in posterior cortices specifically lead to stronger impairments of FC in the alpha range. Allaman et al (2021) revealed that spontaneous α-band interactions of visual areas are associated with the severity of visual field deficits in patients with postchiasmal lesion outside of the occipital lobe.…”
mentioning
confidence: 99%
“…Aging, unhealthy lifestyles such as alcohol consumption, neurodegenerative and infectious diseases are among the reasons for these changes [1][2][3]. In response to these structural changes, the function of the brain change [4]. Researchers use different medical techniques depending on whether they want to study structural or functional changes.…”
Section: Introductionmentioning
confidence: 99%